100 m min−1 Industrial‐Scale Flexographic Printing of Graphene‐Incorporated Conductive Ink. Issue 5 (4th December 2021) - Macadam, Nasiruddin; Ng, Leonard W. T.; Hu, Guohua; Shi, HaoTian H.; Wang, Wenyu; Zhu, Xiaoxi; Ogbeide, Osarenkhoe; Liu, Shouhu; Yang, Zongyin; Howe, Richard C. T.; Jones, Chris; Huang, Yan Yan Shery; et al.
Abstract : Flexographic printing is promising for large‐area electronics due to high print‐speed and roll‐to‐roll capability. There have been recent attempts in using graphene as an active pigment in inks, most notably for slower techniques such as inkjet and screen printing. However, formulation of graphene‐enhanced inks for high‐speed printing and its effect on key metrics have never been investigated. Herein, graphene nanoplatelets (GPs) are incorporated to a conductive flexographic ink without compromising the rheological properties. An industrial scale at 100 m min −1 is printed on paper and polyethylene terephthalate (PET) substrates using a commercial flexographic press, and statistical performance variations are investigated across entire print runs. It is shown that GP‐incorporation improves sheet‐resistance ( R s ) and uniformity, with up to 54% improvement in average R s and 45% improvement in the standard‐deviation on PET. The adhesion on both the substrates improves with GP‐incorporation, as verified by tape/crosshatch tests. The durability of GP‐enhanced samples is probed with a 1000 cyclic bend‐test, with 0.31% average variation in resistance in the flat state on PET between the first and last 100 bends, exhibiting a robust print. The statistically scalable results show that GP‐incorporation offers a cost‐performance advantage for flexographic printing of large‐area conductive patterns without modifications to traditional high‐speed graphics printing presses. Abstract : Herein, high‐speed printing of graphene‐enhanced inks are demonstrated in a commercial, unmodified graphics printer at up to 100 m min −1 . Inclusion of 2.5 wt% graphene in conductive carbon inks improves sheet resistance of printed patterns by up to 54% with a 3% corresponding increase in cost.